Pengaruh Pengembangan Karir, Kompensasi, dan Kepuasan Kerja Terhadap Loyalitas Karyawan Graha Perhutani Jakarta Selatan - Slanika, Erfan Ega; Supiyadi, Dedi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Employee loyalty is a key factor in the sustainability of a company. This study aims to analyze the effect of career development, compensation, and job satisfaction on employee loyalty at Graha Perhutani South Jakarta. A quantitative approach was used with a survey method through a questionnaire distributed to 80 respondents. The data analysis technique uses multiple linear regression with the help of SPSS. The results showed that simultaneously career development, compensation, and job satisfaction have a significant influence on employee loyalty with an R Square value of 35.2%. Partially, job satisfaction has the greatest influence on employee loyalty, followed by compensation and career development. The conclusion of this study is that companies need to increase job satisfaction, implement a fair compensation system, and provide clear career development opportunities in order to increase employee loyalty. Translated with DeepL.com (free version).